إسهامات أصول المالكية في ضبط نوازل الصيرفة الإسلامية - نماذج مختارة- - حمزة زروق.; محمد بن خريف (جامعة محمد بوضياف – بالمسيلة–, 2025)
تم استعراض الأصول التي تميز بها المذهب المالكي، والتي أسهمت في نجاح الصيرفة الإسلامية منذ بدء العمل المصرفي الإسلامي المعاصر، والكشف عن الآراء الاجتهادية لهذا المذهب في المعاملات المالیة التي قدمت حلولا لعقبات وقفت أمام نشاط البنوك الإسلامية في تبنى الحل الإسلامي والتي شاعت وخالطت تفاصيل حیاة الفرد المسلم، لذلك جاء البحث الموسوم بـ: إسهامات أصول المالكية في ضبط نوازل الصيرفة الإسلامية -نماذج مختارة- وصيغت إشكاليته كالتالي: إلى أي مدى ساهمت أصول المذهب المالكي في درك الأحكام الفقهية لبعض نوازل الصيرفة الإسلامية المعاصرة؟ ومن بين أهدافه: تقديم أمثلة واقعية لتطبيق أصول المذهب المالكي في مجال الصيرفة الإسلامية وكذا تحديد مختلف صيغ العقود المالية النازلة في مجال الصيرفة المخرجة شرعيتها على وفق أصول المذهب المالكي "The principles that distinguish the Maliki school were reviewed, highlighting their contribution to the success of Islamic banking since the beginning of contemporary Islamic financial operations. The study also examined the jurisprudential opinions of this school regarding financial transactions, which provided solutions to obstacles that hindered Islamic banks from adopting Islamic financial methods. These solutions became integrated into the details of Muslim individuals’ lives. Thus, the research titled The Contributions of Maliki Principles in Regulating Islamic Banking Challenges - Selected Models was formulated with the following research question: To what extent have the principles of the Maliki school contributed to understanding the jurisprudential rulings of some contemporary Islamic banking challenges? Among its objectives are: providing real-world examples of applying Maliki principles in the field of Islamic banking and identifying various financial contract structures used in Islamic banking, ensuring their legitimacy in accordance with the Maliki school."